Brand wars through brand soldiers: inter-brand community conflict - Seraj Akşit, Zeynep Mina. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
With the digitalization in the marketing realm, consumers have become more interconnected and more powerful to raise their voice through social media environments. This has also prepared the setting, which could not have been established otherwise, for opposing brand communities to come across and engage in rhetorical confrontations to support, protect, and augment the brands they cherish. These confrontations have bred the novel concept of inter-brand community conflict (IBCC), which is the main subject of this dissertation. Even though brand communities are entities that have been thoroughly investigated within consumer culture theory, the concept of inter-communal engagements has been rather uncultivated and this manuscript seeks to explore what IBCC is and why it gets elevated during inter-communal interactions. The study uses the Apple and Android brand competition, or rather war, as the context; and netnography supported with in-depth interviews as the methodology to comprehend how and why the brand communities around these two brands are in constant conflict and what goads brand community members to become voluntary brand soldiers within this dispute. The qualitative approach both defines what IBCC is and yields that differences in communal personalities, corporate strategies, and brand legacies nourish this phenomenon. The study also discusses and further evolves the concepts of mainstream vs. non-mainstream brand communities, voluntary brand soldiering, and the cyclicality of IBCC within the grounds of market competition.
Keywords: Brand name products -- Management.; Branding (Marketing)